2006
DOI: 10.1183/09031936.06.00077205
|View full text |Cite
|
Sign up to set email alerts
|

Influence of body mass index on the response to asthma controller agents

Abstract: The incidence of asthma has been positively associated with obesity. Asthma comprises diverse ''phenotypes'' reflecting heterogeneity in a number of characteristics, including response to therapy. The present authors examined whether body mass index (BMI) influenced the response to placebo, as well as to two asthma controller medications.A post hoc analysis was performed, pooling data from four double-blind, placebo-controlled studies randomising 3,073 moderate asthmatic adults to montelukast (n51,439), beclom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
281
6
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(321 citation statements)
references
References 51 publications
15
281
6
12
Order By: Relevance
“…We know from adults that the response to different asthma medications is influenced by an increasing BMI. 24 The effect of placebo or corticosteroid treatment on asthma symptom-free days was lower in obese patients with asthma, whereas this effect was not seen in treatment with leukotriene antagonists. Data on children with asthma combined with excessive body weight are still scarce.…”
Section: Discussionmentioning
confidence: 97%
“…We know from adults that the response to different asthma medications is influenced by an increasing BMI. 24 The effect of placebo or corticosteroid treatment on asthma symptom-free days was lower in obese patients with asthma, whereas this effect was not seen in treatment with leukotriene antagonists. Data on children with asthma combined with excessive body weight are still scarce.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, the proportion of obese subjects increased with asthma severity step, reaching the peak in the highest asthma severity step (26). Furthermore, several studies showed an inverse relationship between BMI categories and reduction in asthma control, in response to all controller therapies (ICS, antileukotrienes and ICS plus long-acting β agonist in combination) (25)(26)(27)(28)(29). Therefore, obesity can be an important factor that may have influenced the reduced response to Omalizumab in the elderly asthmatics of our study in terms of ACT level and number of exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…Sutherland et al reported a reduced in vitro response to dexamethasone in overweight and obese patients with asthma [98]. In this regard, a retrospective data ana lysis by Peters-Golden et al suggested that obese asthmatics had an attenuated response to inhaled corticosteroids, while obese and nonobese patients had a similar response to leukotriene antagonists [97]. However, adequate comparative clinical trials remain to be performed to determine their comparative effects in this population.…”
Section: Obesitymentioning
confidence: 99%
“…It has been suggested that obese asthmatic patients have an altered response to asthma medications, particularly a reduced response to inhaled corticosteroids [96,97]. Sutherland et al reported a reduced in vitro response to dexamethasone in overweight and obese patients with asthma [98].…”
Section: Obesitymentioning
confidence: 99%